2012
DOI: 10.1143/jjap.51.09le10
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-Induced Photovoltaic Effects in Nd-Doped BiFeO3 Ferroelectric Thin Films

Abstract: Nd-doped BiFeO 3 (BNF) thin films were fabricated on SrRuO 3 (SRO)-coated (100) Nb-doped SrTiO 3 substrates by pulsed laser deposition, and nondoped BiFeO 3 (BFO) thin films were also fabricated similarly for comparison. Then, Nd-doping effects on ferroelectric and photovoltaic properties were evaluated. Polarization-induced photovoltaic effects were observed in both the BFO and BNF solar cell structures with top and bottom electrodes under intense laser illumination. Using Au top electrodes, enhanced photovol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…It was found that the light absorption of the BNFO(100) pc sample has dramatically enhanced in the visible light region (Figures 2c and S2a), although the band gap of BNFO (2.7 eV) is slightly increased compared to that of the BFO sample (2.5 eV), as shown in Figure S2b. A similar band gap of BNFO film was reported by Ukai et al 6 The ΔE VBO of BNFO also enhances, indicating a decrease in conduction band offset (ΔE CBO ) at the heterojunction interface. Thus, the charge transfer efficiency of the BNFO(100) pc sample has been improved.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…It was found that the light absorption of the BNFO(100) pc sample has dramatically enhanced in the visible light region (Figures 2c and S2a), although the band gap of BNFO (2.7 eV) is slightly increased compared to that of the BFO sample (2.5 eV), as shown in Figure S2b. A similar band gap of BNFO film was reported by Ukai et al 6 The ΔE VBO of BNFO also enhances, indicating a decrease in conduction band offset (ΔE CBO ) at the heterojunction interface. Thus, the charge transfer efficiency of the BNFO(100) pc sample has been improved.…”
Section: Resultssupporting
confidence: 83%
“…5 Besides, BFO has opened up a great research opportunity for the development of water splitting technology due to its lead-free nature, 6 high stability, 7 large saturation polarization (∼90 μC/cm 2 ), 8 and small energy band gap (2.1−2.7 eV) 9 compared with other multiferroic materials. The relatively small energy band gap increases the optical absorption efficiency of BFO in the visible light region 6,9 and thus enhances its ability as a visible light driven photocatalyst because almost 50% of the incoming solar energy is occupied by visible radiation. 10 Moreover, BFO has the advantages of provoking the efficiency of electron−hole pair separation and surface potential modification via manipulating the ferroelectric polarization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The density-functional-theory (DFT) calculation and X-ray absorption spectroscopy revealed that the A-site rare-earth lanthanum (La) doping in BFO can reduce the leakage current18. It has been reported that doping can be one of the most effective methods used to improve ferroelectric and magnetic properties19202122, as the Bi-site substitution can effectively control the volatility of Bi atoms with reduction of oxygen vacancies23 and enhancement of photovoltaic effects242526. For photovoltaic applications, the BFO should be able to absorb as much light as possible to generate a photocurrent, which requires a lower band gap and large absorption coefficient27.…”
mentioning
confidence: 99%